ANALISIS PANCASILA SEBAGAI WELTANSCHAUUNG BAGI KEHIDUPAN BERBANGSA - Sugiharto; Dwi Arifin Lubis, Juliana; Rahman, Anisa; Wijaya, Aris; Sartika, Rinny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Pancasila as a weltanschauung has a very important role in directing the behavior and life of Indonesian society. By integrating the noble values ​​of the Indonesian nation, Pancasila becomes a moral compass and guideline in society and the state. The implementation of Pancasila values ​​in national and state life covers various aspects, such as social, political and cultural life. However, the implementation of Pancasila is also faced with various challenges and obstacles, such as limited awareness, limited resources and legal limitations. To overcome these challenges, strong awareness and commitment is needed from the community and government in developing the values ​​of Pancasila and maintaining a peaceful and prosperous national and state life. The approach taken is a literature study by examining several sources that are relevant to the analysis of Pancasila as a part of national life. Based on a literature study approach where the author collects data and information in the form of documents, discussion books, journals, articles and others.